How does an invasive cyprinid can benefit from the hydrological disturbance of Mediterranean temporary streams? - Matono, Paula (2019)
The Iberian Peninsula has been subjected to numerous fish introductions and the colonization of new areas by non-native species is constantly reported. However, there is a lack of knowledge about many aspects of the bio-ecology of these species and their invasive success within the environmental context of Mediterranean temporary rivers. This study aimed to address the following questions: (i) what are the main regional and local environmental drivers influencing fish assemblages and differentiating native from non-native species, particularly A. alburnus?; (ii) what are the environmental and anthropogenic disturbance factors responsible for the occurrence and abundance of A. alburnus?; (iii) is there a pattern in the spatiotemporal distribution of A. alburnus size classes, along the tributaries of reservoirs where the species occurs? Data on fish species, environmental variables, and anthropogenic disturbance were collected in 77 sites of the Guadiana and Sado river basins in the south of Portugal. Additionally, a seasonal sampling was performed along an upstream-downstream gradient of several tributaries from three reservoirs in these river basins. A multivariate analysis and a multi-model approach were used in data analyses. Native and non-native fish assemblages showed different environmental drivers and responses to anthropogenic disturbance levels, though A. alburnus has revealed similarities with native species. The occurrence of A. alburnus was mainly determined by hydrological and morphological disturbances driven by anthropogenic activities. Furthermore, this species apparently performed seasonal movements along the tributaries of several reservoirs, profiting from these lentic habitats as a stepping-stone for further invasions. This study highlighted the wide ecological plasticity of A. alburnus, as it benefits from the anthropogenic hydrological disturbance (induced by reservoirs), and is also able to cope with the natural hydrological disturbance (resulting from the intermittency of these streams), to guarantee and enhance its invasive success in Mediterranean intermittent streams. It also gives a sound contribution to understand the spread of A. alburnus in these vulnerable freshwater ecosystems, and to delineate management measures, namely by identifying critical points in the river network along with prioritizing river restoration measures that benefit native species.